2014
DOI: 10.2500/ar.2014.5.0077
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Inferior Turbinate Reduction Improves Smell Ability of Patients with Chronic Rhinitis and Inferior Turbinate Hypertrophy

Abstract: Radiofrequency inferior turbinate reduction (RFITR) of inferior turbinate hypertrophy (ITH) is an effective way to treat patients with intractable nasal mucosal obstruction. The objective of this study was to assess smell ability, nasal symptoms, inferior turbinate grading (ITG), peak nasal inspiratory flow (PNIF) of patients with chronic rhinitis (CR), and ITH before and after RFITR. Patients with CR and ITH, aged 18–60 years, who underwent RFITR, were prospectively recruited. Smell ability (measured by smell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The study by Assanasen et al just as the present study, found radiofrequency to boost nasal airflow in rhinomanometry and reduce symptoms in the tenth week after the intervention. This study also suggested that the patients' olfactory sensitivity significantly improved in the tenth week (28). The results of the current study, in addition to asserting the previous findings, revealed that radiofrequency was more effective than nasal corticosteroid spray in controlling the symptoms of patients with ITH due to allergic rhinitis.…”
Section: Discussionsupporting
confidence: 83%
“…The study by Assanasen et al just as the present study, found radiofrequency to boost nasal airflow in rhinomanometry and reduce symptoms in the tenth week after the intervention. This study also suggested that the patients' olfactory sensitivity significantly improved in the tenth week (28). The results of the current study, in addition to asserting the previous findings, revealed that radiofrequency was more effective than nasal corticosteroid spray in controlling the symptoms of patients with ITH due to allergic rhinitis.…”
Section: Discussionsupporting
confidence: 83%
“…Inferior turbinate reductions are often performed concurrently, and these data were also collected given the potential to affect NOSE scores postoperatively. 22…”
Section: Methodsmentioning
confidence: 99%
“…Apart from nasal obstruction we also noticed that severity of other symptoms like nasal itching, excessive sneezing, rhinorrhoea, headache, snoring, sense of smell are improved to certain extent as mentioned in other studies. (5,10,11) CONCLUSION: our one year experience of surgical management of the inferior turbinate with radio frequency enables us to state that in our opinion the procedure is relatively simple, fast-it lasts for a few minutes, practically no intra and post-operative complications, well tolerated by the patient, carried out as a day care surgery with satisfactory results.…”
Section: Discussionmentioning
confidence: 87%